Individuals' feedback trading in market and limit trades: Trading behaviours on the Korean stock market. Issue 3 (1st September 2016) - Lee, Hyo-Jeong
ABSTRACT: Using all of individuals' transactions on the Korean stock exchange from 1999 to 2009, I find that Korean individuals engage in negative feedback trading in market trades and positive feedback trading in limit trades. These patterns are stronger for smaller stocks and during down-market. These results indicate that the previously documented contrarian trading by individual investors is driven by their unique behavioural preference instead of their heavy use of limit order. Individuals produce relative gains by engaging in negative feedback trading in market trades, indicating that such trading behaviour is not irrational.